Faktor –faktor yang mempengaruhi kelengkapan pengungkapan laporan keuangan pada perusahaan property dan real estate yang terdaftar di bursa efek indonesia periode 2009 - 2011 - Wiwik Pujiati; Azwir Nasir; Poppy Nurmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to test the effect of the current ratio, net profit margin, debt to asset ratio, firm size, firm age, and the share of public ownership toward completeness of the disclosure of financial statements. The data used in this research is secondary data from annual financial reports of property & real estate company in 2009 - 2011 were obtained from the Indonesia Stock Exchange. The selection of the sample using purposive sampling. Based on the criteria, obtained a sample of 33 firms in this research. While the analysis tool used is multiple linear regression with the T-Test, to know how the effects of the independent variables toward dependent variable partially and R2 test to know the level of relationship of independent variables toward dependent variable. The research result showed that net profit margin, debt to asset ratio and the share of public ownership have a significant effect on the completeness of the disclosure of financial statements based on net profit margin with p value 0.010, debt to asset ratio of 0.024 and the share of public ownership of 0.000 from the α 0,05, but other variables such as current ratio, firm size and firm age does not affect the completeness of the disclosure of financial statements. The coefficient of determination of this research is 43.70%.Keywords : completeness of the disclosure of financial statements. current ratio, net profit margin, debt to asset ratio, firm size, firm age, and the share of public ownership